ROLE OF INDICATORS OF THE HEMOSTASIS IN PATHOGENESIS ESOPHAGEAL AND GASTRIC BLEEDINGS AT PORTAL HYPERTENSIA AT CHILDREN - Дударев, Вадим Александрович; Галактионова, Марина Юрьевна (Mother and Baby in Kuzbass, 2018)
The article analyzes the examination of 67 children with extrahepatic block of portal hypertension. To provide evaluation of hemostasis all children were determined in coagulative, fiber thrombocytic hemostasis, the intensity of fibrinolysis and physiologic anticoagulants. The patients were divided into two groups, one of them is with escape of blood from the esophageal veins, others are not. The parameters of the extended coagulogram allowed to characterize the activity of natural anticoagulants, fibrinolysis system, coagulation factors, aggregative activity of platelets (thrombocytes).Most patients from both groups were revealed a higher activity, an increased concentration of Willebrand factor, an impaired aggregative capability of platelets with ADP and ristocetin. There were less frequent changes such as an increase in the activity of factor VIII and in the concentration of D-dimer, inhibition of XII-dependent fibrinolysis. As the result of the correction of hemostasis in hemostatic indicators were observed chronometric normocoagulation with a slight deficit of factors that form prothrombinase combined with a slight increase the blood plates count with their normal aggregation function and mild endotheliosis, and with a normal level of progressive antithrombins.
Keywords: hemostasis; portal hypertension; children